Penguatan Karakter Konselor Islam Profesional Melalui Pelatihan Konseling Sebaya Bagi Calon Konselor Islam - A. Said Hasan Basri; Muhsin Kalida (IGAKERTA Publisher, 2024)
This community service activity aims to strengthen the character of professional Islamic counselors through peer counseling training for prospective Islamic counselors. This implementation method uses training methods using lecture strategies, roleplay methods, and simulation methods. This community service activity was carried out at IAIN Syaikh Abdurrahman Siddik Bangka Belitung. The results of this activity show an increase in understanding of the character of professional Islamic counselors for prospective Islamic counselors through peer counseling training by 85%.